2018
DOI: 10.1021/acsnano.8b03378
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Registration of Sub-10 nm Features Based on Subzero Celsius Spin-Casting of Self-Assembling Building Blocks Directed by Chemically Encoded Surfaces

Abstract: For low-cost and facile fabrication of innovative nanoscale devices with outstanding functionality and performance, it is critical to develop more practical patterning solutions that are applicable to a wide range of materials and feature sizes while minimizing detrimental effects by processing conditions. In this study, we report that area-selective sub-10 nm pattern formation can be realized by temperature-controlled spin-casting of block copolymers (BCPs) combined with submicron-scale-patterned chemical sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…25,26 In addition, Lee et al selectively deposited block copolymers on patterned surfaces via careful temperature control. 27 Despite promise, there still remains significant uncertainty surrounding the design rules that govern spin dewetting as a function of material selection and processing. Here, we systematically investigate SAMpromoted spin dewetting using homogeneous (SiO 2 ) and heterogeneous (Cu/SiO 2 ; TiN/SiO 2 ) substrates that are relevant to the microelectronics industry.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 In addition, Lee et al selectively deposited block copolymers on patterned surfaces via careful temperature control. 27 Despite promise, there still remains significant uncertainty surrounding the design rules that govern spin dewetting as a function of material selection and processing. Here, we systematically investigate SAMpromoted spin dewetting using homogeneous (SiO 2 ) and heterogeneous (Cu/SiO 2 ; TiN/SiO 2 ) substrates that are relevant to the microelectronics industry.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To address this opportunity, our attention was drawn to a technique known as spin dewetting, which results in the local segregation of polymers during spin coating and requires no postprocessing or additional steps to generate patterns. , Past work has highlighted the simplicity of spin dewetting in comparison to more complex patterning methodologies . Bhandaru et al explored using topographic poly­(dimethylsiloxane) substrates and demonstrated an impressive array of resulting polymer structures depending on prepattern dimensions and coating conditions. , In addition, Lee et al selectively deposited block copolymers on patterned surfaces via careful temperature control . Despite promise, there still remains significant uncertainty surrounding the design rules that govern spin dewetting as a function of material selection and processing.…”
Section: Introductionmentioning
confidence: 99%
“…The S-CSC procedure with a block-copolymer was a uniform micro-pattern form-factor for nanoscale patterning via a simple solution-based spin casting procedure. 13 …”
Section: Nanopatterning Of Sbms Using Optical Lithographymentioning
confidence: 99%
“…Here, we introduce state-of-the-art patterning techniques of SBMs to fabricate micro-to-nanometer scale patterns. This work introduces the printing methods, 11,12 solution ordering from surface treatment, 13 nano-imprinting, 14,15 transfer printing, 16,17 and modied photolithography method 18,19 to explain the current state of the patterning technology of SBMs. Additionally, various applications, which include various optoelectronics with integrated patterns, are introduced to explain the effects of each patterning procedure.…”
Section: Introductionmentioning
confidence: 99%
“… 26,34 Much attention has thus been focused on this BCP and related ones with incorporated segments to improve their performance in next-generation lithography. 35,36 However, to date, it has remained a formidable challenge to obtain normally aligned cylindrical or lamellar domains within BCP films with small feature sizes on versatile substrates by rapid thermal annealing (such as several minutes) at low temperatures.…”
Section: Introductionmentioning
confidence: 99%